Characteristics and Outcome of Ear, Nose, Throat-Head and Neck Emergency Surgeries in a Tertiary Care Center: An Observational Study - Rijal, Krishna Chandra; Gautam, Shreya; Ghimire, Bibek; Koirala, Krishna Prasad; Khadka, Adarsha; Raj Kafle, Binaya; Sapkota, Sagun (Journal of College of Medical Sciences-Nepal, 2025)
Background Emergency Surgeries are those that is required to deal with an acute threat to life, organ or tissue caused by different disease process or complication of a surgical or other interventional procedure. Ear, Nose, Throat - Head and Neck emergency (ENT- HNS) surgeries are carried out to reduce morbidity and mortality. This study aimed to analyze the pattern and outcome of ENT-HNS emergency surgeries in a tertiary care center of western Nepal. Methods An observational study conducted among emergency surgery patients operated in the Department of ENT-HNS of a tertiary care center from January 2021 to December 2023. Ethical approval was received from the Institutional Review Committee of the Institute (MCOMS/IRC/634/GA). The total sampling method was used. Statistical Package for the Social Sciences (SPSS Version 18) was used for data analysis. Results Out of total 458 patients having operation in department, 138 (30.13%) were emergency surgeries. Among 138 patients, 82 (59.42%) were males and 56 (40.58%) were females. Most common emergency surgery performed was rigid esophagoscopy with removal of foreign body 53(38.40%). Regarding outcome of surgery, 130 (94.22%) cases have favorable outcome (p<0.001) whereas 8 (5.78%) cases have unfavorable outcome (p<0.001). Conclusions Though emergency surgical procedures reduce morbidity and mortality but they are also not free of complications. Emergency surgery accounts for one third of the total ENT and HNS surgeries and overall complications rate of the emergency procedures accounts for 3.62% in our center.